The Usborne Internet-linked Book Of Astronomy & Space - Miles, Lisa; Smith, Alastair (London Usborne Publishing Ltd., 2001)
This guide is based on contemporary information from astronomers around the world, and space probes around the galaxy. It contains illustrations of exploding stars and how black holes are formed, star maps so the reader can navigate the night sky, and recommended internet links.
Keywords: Astronomy and Space